ANALISIS PENYEBAB KETERLAMBATAN MULAI OPERASI PERTAMA PASIEN ELEKTIF DI INSTALASI BEDAH SENTRAL RSAM - Muthia Sukma; Masrul Masrul; Rima Semiarty (Universitas Fort De Kock, 2019)
AbstractIntroduction : Operating room eficiency can be assessed using 6 indicators, one of which is the delay in starting the first elective surgery. From the results of preliminary research in the operating room of the Central Surgical Installation (CSI) RSUD dr. Achmad Mochtar (RSAM) Bukittinggi in January and February 2019 showed that 81% of elective surgeries were delayed. Delay ranged from 30 minutes to several hours. Objective: To find out what causes the delay in begining the first elective surgery in the operating room of the Central Surgery Installation at RSAM in 2019 in terms of input, process and output.Method: Qualitative research using the Framework Analysis method was conducted in the operating room of the CSI RSAM. The study began in April until October 2019Conclusion: The reason for the delay in begining the surgery in terms of HR input is that the leadership in CSI is not maximized, lack of discipline and commitment of the operator doctor and anesthesiologist, the anesthesiologist's schedule is not optimized, lack of registration officers, no optimal settings for radiographer for operating rooms and the lack of skills. The problem with SOP inputs is that there are still incomplete SOPs and not yet optimal implementation of existing SOPs. In the infrastructure input the problem is in the distance from the patient's ward to the operating room, CSSD is not integrated to the operating room and picking up surgery clothes and linen to CSSD is late. From the process factor, there are obstacles in the process of delivering patients to the operating room, the arrival time of the surgeon/operator and anesthesiologist are behind schedule, the lack of optimal monitoring and evaluation, and the lack of optimal implementation of reward and punishment. Output shows that from 40 firsts surgery schedules, 35 surgeries were delayed (87.5%) and only 5 operations were carried out on time according to the schedule (12.5%).Keywords: Efficiency, Operating Room, Monitoring, Reward, Punishment